Microalbuminuria: A Predictor of Outcome in Critically ill Patients in Intensive Care Units (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Diffuse endothelial dysfunction in physical, chemical or infectious insult to the host leads to an increase in systemic capillary permeability. The renal component manifests as Microalbuminuria. The degree of Microalbuminuria correlates with the severity of the acute insult and the quantification of which may serve to predict outcome in critically ill patients.Objectives: To evaluate whether the degree of Microalbuminuria could predict outcome in critically ill patients or not.Settings and Study design: This cohort study was carried out in the 20 bed mixed Medical-Surgical Intensive Care Unit of Dhaka Medical College Hospital. A total 60 patients were purposively recruited for this study. In our study, we included all adult critically ill patients aged 18 years or more admitted in ICU after fulfilling the criteria of critically ill patients and who stayed for more than 24 hours. Patients with pregnancy, menstruation, anuria, macroscopic haematuria, pre-existing kidney disease, were excluded. Spot urine samples were collected by ICU nurses at 24 hrs of admission, for the quantification of Albumin Creatinine Ratio, which was referred to as ACR. The outcome of the patient was classified as death and discharge/ survival. Maximum follow up was done for 15 days. Patients discharged within this 15 days, were considered as survival.Results: Patients were divided into two groups, Group-I: subjects (exposed): Patients having Microalbuminuria. Group-II: control (unexposed): Patients having no Microalbuminuria. In this study, Relative Risk was calculated for risk measurement and to assess the strength of association between the patients having Microalbuminuria and outcome and the calculated relative risk was 2.08. It indicates that the presence of Microalbuminuria is a risk factor for the critically ill patients. Chi-square test was used to compare categorical outcomes and for hypothesis testing. The test statisticis11.94 and p=